Pharmacodynamics and pharmacokinetics of snake antivenom - Bhagya Nikapitiya (Sri Lanka Journal of Medicine, 2018)
Intact or fractionated immunoglobulins are used as snake antivenom to treat snake envenomation. Intravenously administered antivenom binds with snake toxins in the circulation and neutralizes the toxins. Binding of antivenom to venom in the central compartment prevents the distribution of venom to the peripheral tissues and enhances the elimination of venom. Reduction of antivenom concentration in the central compartment is due to both distribution to the peripheral tissues and elimination. Pharmacokinetics of snake antivenom varies among the three different types of immunoglobulins, namely whole IgG, F(ab’)2 and Fab. Pharmacokinetics of F(ab’)2 antivenom is best described by two compartment model with zero order input and linear elimination kinetics. Fab and F(ab’)2 antivenom with smaller molecular masses have a larger volume of distribution than whole IgG antivenom. A biphasic decline of intravenously administered whole IgG and F(ab’)2 antivenom has been observed.